Blood product transfusion and lung transplant outcomes: A systematic review. Issue 10 (8th July 2021) - Klapper, Jacob A.; Hicks, Anne C.; Ledbetter, Leila; Poisson, Jessica; Hartwig, Matthew G.; Hashmi, Nazish; Welsby, Ian; Bottiger, Brandi A.
Abstract: The perioperative transfusion of blood products has long been linked to development of acute lung injury and associated with mortality across both medical and surgical patient populations. 1, 2 The need for blood product transfusion during and after lung transplantation is common and, in many instances, unavoidable. However, this practice may potentially be modifiable. 3 In this systematic review, we explore and summarize what is known regarding the impact of blood product transfusion on outcomes following lung transplantation, highlighting the most recent work in this area. Overall, the majority of the literature consists of single center retrospective analyses or the work of multicenter working groups referencing the same database. In the end, there are a number of remaining questions regarding blood product transfusion and their downstream effects on graft function and survival.